A Work Behaviour Analysis of Executive Coaches - Glenn Newsom; Eric B. Dent (International Journal of Evidence Based Coaching and Mentoring, 2011)
This study has three main purposes. First, it introduces the Executive Coaching Work Behaviour Survey and takes the initial steps in validating this instrument. It then explores the frequency of specific work Behaviours executive coaches use in their client interactions and examines the variability in these behaviours based on demographic factors. The Executive Coaching Work Behaviour Survey is shown to measure three factors: Professional Coach Activities, Goal Setting and Attainment Activities, and Relationship Activities. One hundred and thirty executive coaches affiliated with a major global leadership training and development organization were surveyed. Results indicate that the most frequent coaching behaviours are (1) establishing trust, honesty, and respect (2) using open-ended questions, and (3) clarifying and understanding client concerns and challenges. Significant differences in coaching behaviour occur based on some demographic variables measured. For example, women score higher than men in Relationship Activities behaviours, coaches with only a Bachelor’s degree score higher than coaches with a doctoral degree in Professional Coach Activities, and coaches with business-related educations perform more Professional Coach Activities than coaches with counseling-related educations. An implication of this study is that competencies needed to achieve professional level performance as an executive coach are not derived from particular educational or work-related experiences.